SIMPLE-G A Gridded Economic Approach to Sustainability Analysis of the Earth$1 (Bs Land and Water Resources /s - Haqiqi, Iman.; Hertel, Thomas W.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This is an open access book. Crafted for both the economist and the curious mind, this book introduces a novel approach to blending economic and biophysical sciences to enable multi-scale analysis of a range of sustainability challenges confronting the world$1 (Bs land and water resources at both local and global scales. It focuses specifically on the interface between the environment and food systems, utilizing economic theory to structure the overall framework. However, within the SIMPLE-G framework, there is ample room to incorporate fine-scale biophysical knowledge from agronomy, climate science, ecology, geography, hydrology, as well as a range of socioeconomic considerations. This enables multi-scale analyses incorporating grid cells that can vary in size from 250 meters to sub-regional scales. This, in turn, allows for investigation of global change drivers$1 (Bimpacts on local sustainability, as well as feedbacks from local sustainability policies to regional and global outcomes. The book opens with a foreword by a prominent sustainability scientist, Prof. Navin Ramankutty, and proceeds in five parts covering, respectively: (1) introduction and overview, (2) basic economic theory underpinning SIMPLE-G, (3) the SIMPLE-G framework, including structure, data, parameters, computer implementation, and validation, (4) eight diverse applications of the SIMPLE-G framework, covering a range of geographies and sustainability challenges, and (5) a forward-looking chapter on future directions. The book provides step-by-step guidance on building and utilizing gridded models with real-world case studies demonstrating practical applications which will facilitate its use by academics, practitioners, and students conducting research on climate impacts, land-use, water resource management, food security, poverty, equity, nutritional outcomes, and overall sustainability.s
Chapter 1 Introduction -- Chapter 2 SIMPLE Economic Theory -- Chapter 3 Grid-level Analysis Using SIMPLE-G -- Chapter 4 Equilibrium Conditions and General Assumptions for a Quantitative Geospatial Economic Model -- Chapter 5 SIMPLE-G Model Specification -- Chapter 6 Benchmark Data -- Chapter 7 Behavioral Parameters -- Chapter 8 Computation and Baseline -- Chapter 9 Model Validation -- Chapter 10 The R&D Cost of Climate Mitigation in Agriculture -- Chapter 11 Gridded Implications of Total Factor Productivity Growth -- Chapter 12 Local Groundwater Sustainability Policies and Global Spillovers -- Chapter 13 The Role of Labor Markets in Determining the Efficacy and Distribution Impact of Sustainability Policies -- Chapter 14 Tackling Policy Leakage and Targeting Hot Spots Could Be Key to Addressing the (3z(BWicked(3y (BChallenge of Nutrient Pollution from Corn Production in the United States -- Chapter 15 The Role of Transportation Infrastructure Expansion in the Transmission of Global Crop Price Shocks to the Brazilian Agriculture -- Chapter 16 Global Groundwater Sustainability and Virtual Water Trade -- Chapter 17 Interplay Between the Pandemic and Environmental Stressors -- Chapter 18 Future Directions.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Sustainability; Environmental economics; 9; Water; Hydrology; Sustainability; Environmental Economics; Applied Statistics; Water